2018
DOI: 10.5853/jos.2018.01550
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions in Children and Adults with Moyamoya Vasculopathy: A Systematic Review and Meta-Analysis

Abstract: Background and PurposePatients with moyamoya vasculopathy (MMV) may experience cognitive impairment, but its reported frequency, severity, and nature vary. In a systematic review and metaanalysis, we aimed to assess the presence, severity, and nature of cognitive impairments in children and adults with MMV. MethodsWe followed the MOOSE guidelines for meta-analysis and systematic reviews of observational studies. We searched Ovid Medline and Embase for studies published between January 1, 1969 and October 4, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
1
37
1
Order By: Relevance
“…Longer duration of symptoms, cerebral infarction, and bilateral involvement had been suggested to associate with poorer cognitive performance (21,(24)(25)(26). However, these associations were not significant in a meta-analysis study (3). In our study, only radiologically-evident cerebral infarction was associated with lower cognitive index scores.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Longer duration of symptoms, cerebral infarction, and bilateral involvement had been suggested to associate with poorer cognitive performance (21,(24)(25)(26). However, these associations were not significant in a meta-analysis study (3). In our study, only radiologically-evident cerebral infarction was associated with lower cognitive index scores.…”
Section: Discussioncontrasting
confidence: 86%
“…Consecutive pediatric MMD patients who were admitted to Beijing Tiantan Hospital from July 2017 to March 2019 and met the inclusion criteria were prospectively enrolled in the current study. The inclusion criteria were as follows: (1) Patients were aged between 6 and 16 years old; (2) Patients did not accept previous revascularization surgery; (3) Patients were cooperative to WISC-IV examination. The diagnosis of MMD was confirmed by digital subtraction angiography (DSA) or magnetic resonance angiography (MRA) based on a 2012 guideline on MMD (12), and only bilateral MMD were included.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ΔICA-MTT may be used as a quantitative index during serial observation. In previous studies, ischemic-onset, abundant ICA moyamoya vessels, Suzuki stages 3-4, and preoperative neurological status were reported to be associated with better neoangiogenesis and more favorable long-term outcome after revascularization surgery for MMD [6,[34][35][36]. However, these factors were not quantitative and mainly based on the preoperative features, which would be inappropriate for serial evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Karzmark et al studied cognitive function in 36 cases of MMD and found that the incidence of cognitive impairment was about 31% (11/36), but most degree of them were mild 6. Kronenburg et al found that the incidence of cognitive impairment in adult MMD was about 30%, and the median IQ was 95 (94–99) 29. In our study, the average IQ of adult MMD was 97 (97.27±14.36), while the average value of healthy controls was 106 (106.26±9.44).…”
Section: Discussionmentioning
confidence: 99%